One life one ummah: a preservation of life - Ismail, Mohd Helmie; Abu Hasan, Muhammad Abdus-Syakur (Sultan Ahmad Shah Medical Centre (SASMEC), IIUM, 2024)
Cardiopulmonary arrest is one of the unpredicted events for all groups of patients who come to the hospital, especially in the emergency department. In the emergency department of SASMEC @IIUM,l we manage about 3500 to 4000 patients per month, and about 1% to 2% of them present with cardiac arrest on arrival to the hospital or even at the pre-hospital scene that requires immediate resuscitation. The well-trained staff is crucial to perform immediate and effective measures to improve survival rate. The chapter aims to share 2-year challenging experience to train our staff on basic life support and perform it effectively, the process flow towards the main goal, the development of effective and best BLS modules, monitoring the program and the outcomes, and reflections for future plan.